Comparison of two methods for coating piezoelectric crystals - GOMES, MT
Quartz piezoelectric crystals were coated with triethanolamine using two procedures: spray and syringe methods. The reproducibility of both coating methods was evaluated comparing the relative standard deviation of batches of four crystals coated by each of the procedures. The relative standard deviation obtained with the spray method is a hyperbolic function of the coating frequency and is, at least, three times lower than the one calculated from results of the syringe method, which is not frequency dependent. An explanation for the poorer reproducibility of the syringe method is given, based on the radial sensitivity theory and the non-uniformity of the coating distribution over the crystal, as evidenced by microscopic photographs.